Use of the pictet-spengler reaction for the synthesis of 1,4-disubstituted-1,2,3,4-tetrahydro-beta-carbolines and 1,4-disubstituted-beta-carbolines: formation of gamma-carbolines - Kusurkar, Radhika S.; Alkobati, Nabil A. H.; Gokule, Anita S.; Puranik, Vedavati G. (Tetrahedron, 2008)
Microwave-assisted conjugate addition of indole on nitro-olefins furnished nitro compounds, which were reduced to tryptamines. Further, by using Pictet-Spengler condensation, new 1,4-disubstituted-1,2,3,4-tetrahydro-beta-carbolines were synthesized in diastereoselective manner. Dehydrogenation of the tetrahydro-beta-carbolines produced new 1,4-disubstituted-beta-carbolines. As a new observation, in some of the cases, Pictet-Spengler condensation and dehydrogenation gave two products, namely 1,4-disubstituted-beta-carbolines and 1,4-disubstituted-gamma-carbolines. A mechanism is proposed for this observation. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3; 4-Disubstituted-1; 4-disubstituted-beta-carboline; 4-disubstituted-gamma-carboline; 4-tetrahydro-beta-carboline; 4-tetrahydro-gamma-carboline; Pictet-Spengler reaction